The Canadair-I.A.M. Productivity Improvement Plan - Peach, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This paper presents the experience of Canadair-I.A.M. Productivity Improvement Plan.